The political economy of private firms in China - Guo, Di; Jiang, Kun; Kim, Byung-Yeon; Xu, Chenggang (Elsevier, 2014)
The sweeping change in political economy associated with the spectacular growth of the private sector in China is rarely studied empirically in the economics literature. This paper fills this gap. The central subject of this paper is the nature of the political economy of the Chinese private sector and of the Communist Party of China during these changes. We empirically examine the dynamics of rent creation from the Party membership and other political connections when the regime is changed from anti-capitalistic to procapitalistic. Endogeneity problems are addressed. We identify the causality of rents and the political connections of private entrepreneurs.